Behavioral and psychological symptoms and cognitive decline in patients with amnestic MCI and mild AD: a two-year follow-up study. (16th January 2015) - Pocnet, Cornelia; Antonietti, Jean-Philippe; Donati, Alessia; Popp, Julius; Rossier, Jérôme; von Gunten, Armin
ABSTRACT: Background: Mild cognitive impairment (MCI) has been defined as a transitional state between normal aging and dementia. In many cases, MCI represents an early stage of developing cognitive impairment. Patients diagnosed with MCI do not meet the criteria for dementia as their general intellect and everyday activities are preserved, although minor changes in instrumental activities of daily living (ADL) may occur. However, they may exhibit significant behavioral and psychological signs and symptoms (BPS), also frequently observed in patients with Alzheimer's disease (AD). Hence, we wondered to what extent specific BPS are associated with cognitive decline in participants with MCI or AD. Methods: Our sample consisted of 164 participants, including 46 patients with amnestic (single or multi-domain) MCI and 54 patients with AD, as well as 64 control participants without cognitive disorders. Global cognitive performance, BPS, and ADL were assessed using validated clinical methods at baseline and at two-year follow-up. Results: The BPS variability over the follow-up period was more pronounced in the MCI group than in patients with AD: some BPS improve, others occur newly or worsen, while others still remain unchanged. Moreover, specific changes in BPS were associated with a rapid deterioration of the global cognitive level in MCI patients. In particular, an increase of euphoria, eating disorders, and aberrant motor behavior, as well as worsened sleep quality, predicted a decline in cognitive functioning. Conclusions: Our findings confirm a higher variability of BPS over time in the MCI group than in AD patients. Moreover, our results provide evidence of associations between specific BPS and cognitive decline in the MCI group that might suggest a risk of conversion of individuals with amnestic MCI to AD.